Corporate decarbonization strategies and carbon accounting standards: implementation learnings to inform standard revisions - Lahd, Holly (Frontiers in Sustainable Energy Policy, 2025)
The corporate commitment to reducing greenhouse gas (GHG) emissions has gained significant traction, with over 11,000 companies committing to reduce their corporate emissions. This paper critically examines two prevalent corporate climate strategies: renewable energy power purchase agreements (PPAs) and supplier engagement initiatives, highlighting their alignment with existing GHG Protocol accounting standards and company implementation considerations around internal approval processes, business operation impacts, and transaction costs. The analysis reveals that PPAs are successful due to their clear recognition in accounting standards and minimal impact on core business operations. Conversely, supplier engagement programs, despite their endorsement by initiatives like the Science Based Targets Initiative, struggle to deliver scope 3 inventory reductions emissions due to mismatched data and high transaction costs. The paper underscores the necessity for corporate climate standard setters to consider the realities of company accounting and decarbonization strategy practices as standards undergo major revisions. By integrating these implementation considerations, the effectiveness of voluntary GHG emissions accounting and target-setting systems can be improved, ultimately contributing to more significant emission reductions.